GREEN HOTEL SEBAGAI DAYA SAING SUATU DESTINASI - Sinangjoyo, Nikasius Jonet (JURNAL NASIONAL PARIWISATA, 2013)
The goal of the research is describing the green hotel application program of the hotel industries in Yogyakarta, creation of competitiveness in tourism destination. Subject of the research is whole member of Indonesia Hotel & Restaurant Association, (PHRI) Yogyakarta, which classified as four and five star hotel, and have an environment document or green hotel certificate. This study is a descriptive qualitative research. The research shows that the green hotels standard application in Yogyakarta, in general have done environmentally friendly practice, but there are a few problems such as inconsistency done of hotel staff, consciousness of guest is less, not enough socialization and some have perception that green hotel application need high cost. Such problems necessary to be resolved by training socialization, build commitment, make green team and apply green tourism marketing strategy.